2022
DOI: 10.3855/jidc.17077
|View full text |Cite
|
Sign up to set email alerts
|

ITS-RFLP optimization for dermatophyte identification from clinical sources in Alagoas (Brazil) versus phenotypic methods

Abstract: Introduction: Dermatophytoses are superficial mycoses, and the identification of their etiological agents is routinely performed by culture and microscopic features, which is time-consuming and relies on personnel expertise. Molecular approaches have been developed to provide faster and reliable results; therefore, this study aimed to identify dermatophytes isolated from Alagoas state patients, employing phenotypical and molecular methods. Methodology: Clinical samples for morphological identification we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Recent studies have shown that this technique serves as a valuable tool for identifying a variety of pathogenic fungal species, such as Cryptococcus sp., Dermatophytes, Paracoccidioides sp., and Candida sp. [20,[29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that this technique serves as a valuable tool for identifying a variety of pathogenic fungal species, such as Cryptococcus sp., Dermatophytes, Paracoccidioides sp., and Candida sp. [20,[29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study published by Fonseca in 2022 [30] highlighted the efficiency of the ITS region in a simple digestion RFLP assay for identifying species of dermatophytes of the genera Trichophyton sp. and Microsporum sp.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular diagnosis for the dermatophytes is often by nucleic acid amplification techniques targeting the ITS and CHS1 regions [ 32 , 38 40 ]. Several modifications of PCR like multiplex techniques [ 41 43 ], nested PCR [ 44 ], PCR-ELISA [ 45 ], restriction digestion of the PCR products [ 46 , 47 ] or real time detection [ 48 , 49 ] for these targets are reported. The use of ITS and chitinase based molecular detection methods have proven valuable [ 50 ].…”
Section: Discussionmentioning
confidence: 99%